ANALISIS PENGARUH INVESTASI PENANAMAN MODAL DALAM NEGERI (PMDN) DAN PENANAMAN MODAL ASING (PMA) TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAMBI - Nuraini Nuraini (Universitas Batanghari Jambi, 2016)
In Indonesia is a developing country with potential to become a developed country, quite a lot of developed countries such as Singapore, Japan, Korea and Amarica began to look at the market in Indonesia to invest. Her high charm for Indonesia natural resources for the promotion to attract wealthy investors to invest ber. Invesment is crucial to economic growth, High Invesment value will have a great impact on the economy of the nation and its reverse. In Inndonesia the rate of growth of domestic and foreigh invesments in Jambi Province in 2000. 2014 on average 9,37 % and 12,27 %, while the influence of domestic and foreigh invesments to economic growth in nthe last 15 tears simultaneously by 54,50 % patialy respectively 59 % and 51,10 % is very significant and positive under the alpha 5 % le 0,011 or 1,1 % and 0,022 %Keyword : investasi, PMA, PMDN.